ADVANCE CARE PLANNING IN ADULT AND PEDIATRIC CANCER PATIENTS: A REVIEW - Yağmur Berktaş; Ülkü Miray Yıldırım; Rejin Kebudi (Sabiad)
Advance care planning (ACP) aims to support patients regardless of age or stage of health to understand and share personal values, goals in life, and future medical care preferences. This process which may be started at any time should be reviewed at periodical intervals depending on individuals’ medical conditions. According to previous research, end-of-life care is a source of deep concern for many people who want to ensure active involvement in decision-making processes. Compared to other patient groups, individuals suffering from advanced cancer may have different levels of willingness regarding being a part of ACP discussions, as evidence shows. The barriers to ACP, the fear surrounding ACP, cultural differences, and previous health experiences have generated differences of opinion on the use and implementation of ACP. Across the world, palliative care principles and advance care planning are developing in the field of Medical Oncology. This review aimed to present the most important features of ACP in adult and pediatric cancer patients and to incorporate this concept to Turkish literature.